Pengaruh Pengaruh Media Poster pada Pengetahuan dan Praktik Personal Hygiene Penjamah Makanan di Katering Senjani Kitchen Malang : Poster Personal Hygiene: Media untuk Pengetahuan dan Praktik Penjamah Makanan - Salsabila Fauziah Rahayu; Nurul Hakimah; Carissa Cerdasari (Amerta Nutrition, 2022)
Background: Catering is way to fulfill the need for food. Catering is an institutional food management because it produce large amounts of food. Large quantities of food handlers also required and increasing the potential of food contamination. Prevention can be done by applying personal hygiene according to Permenkes RI No. 1096/Menkes/PER/VI/2011. Enhancement of knowledge and practice are needed to improve the application of personal hygiene with poster installation. Senjani Kitchen Catering is a catering service located in Malang. The preliminary study indicate that the food handlers have not implemented personal hygiene properly. Objectives: This study aims to analyze poster’s effect on Senjani Kitchen Malang food handlers’ personal hygiene knowledge and practices. Methods: This research is a descriptive study with quantitative approach used pre-experimental research with one group pretest posttest design. Posters were installed in the work area with sample of 5 food handlers. Results: The average scores of food handlers’ personal hygiene knowledge before the intervention was 70.7 (enough). After the intervention, it increased to 82.7 (good). The average scores of food handlers’ personal hygiene practice before the intervention was 55.7 (less). After the intervention, it increased to 73.0 (enough). Conclusions: There is an increased value of food handlers’ personal hygiene knowledge and practices after placing posters in the work area.